2022
DOI: 10.1016/j.japh.2021.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The voices of community pharmacists during the COVID-19 pandemic in Puerto Rico

Abstract: Background Community pharmacists have provided healthcare services uninterruptedly throughout the COVID-19 pandemic. However, their public health role is often overlooked. Objectives The purpose of this manuscript is to discuss the roles and the coping mechanisms of community pharmacists working during the COVID-19 pandemic in Puerto Rico. Methods A cross-sectional study, using an electronic survey, was conducted to assess the community pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…And yet, similar to findings in Pakistan [47], some participants noted that more guidance and a clearer regulatory framework are needed to support pharmacies and enable them to contribute to pandemic response efforts. Indeed, limited coordination and recognition of the important role of the private sector, including pharmacies, has been a long-standing challenge to effective PLOS GLOBAL PUBLIC HEALTH public health action in many countries, and has been a major shortcoming of pandemic preparedness in the past [48] and during the COVID-19 crisis [3,[49][50][51]. In a study in Puerto Rico, for example, pharmacists were resentful and outraged they were excluded from all government schemes aimed at recognizing and incentivizing essential workers and health professionals, despite providing continued service since the start of the COVID-19 pandemic [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And yet, similar to findings in Pakistan [47], some participants noted that more guidance and a clearer regulatory framework are needed to support pharmacies and enable them to contribute to pandemic response efforts. Indeed, limited coordination and recognition of the important role of the private sector, including pharmacies, has been a long-standing challenge to effective PLOS GLOBAL PUBLIC HEALTH public health action in many countries, and has been a major shortcoming of pandemic preparedness in the past [48] and during the COVID-19 crisis [3,[49][50][51]. In a study in Puerto Rico, for example, pharmacists were resentful and outraged they were excluded from all government schemes aimed at recognizing and incentivizing essential workers and health professionals, despite providing continued service since the start of the COVID-19 pandemic [3].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, limited coordination and recognition of the important role of the private sector, including pharmacies, has been a long-standing challenge to effective PLOS GLOBAL PUBLIC HEALTH public health action in many countries, and has been a major shortcoming of pandemic preparedness in the past [48] and during the COVID-19 crisis [3,[49][50][51]. In a study in Puerto Rico, for example, pharmacists were resentful and outraged they were excluded from all government schemes aimed at recognizing and incentivizing essential workers and health professionals, despite providing continued service since the start of the COVID-19 pandemic [3]. In contrast, evidence suggests that countries that have engaged with the private sector, through for example, purchasing arrangements or the rapid adaptation of existing policies around the management of drug supplies [37], have been able to implement more effective COVID-19 response measures [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vaccine application and testing by community pharmacists showed divergence in acceptance for the service. In addition to easy accessibility of these services to the population, some authors reported the willingness of professionals to test and immunize, contributing to the information, advertising, and promotion of vaccines, 26 , 27 , 29 , 30 while others showed dissatisfaction with this aspect, due to overload, lack of support, training, or confidence in the vaccine. 28 …”
Section: Main Strategies For Addressing Covid-19mentioning
confidence: 99%
“…The need for education and training related to COVID-19 was an important finding of the studies. 20 , 22 , 23 , 29 , 31. , 32.…”
Section: Main Strategies For Addressing Covid-19mentioning
confidence: 99%